Priming with HDAC Inhibitors Sensitizes Ovarian Cancer Cells to Treatment with Cisplatin and HSP90 Inhibitors - Ana J. Rodrigues Moita (International Journal of Molecular Sciences, 2020)
Ovarian cancer is the fifth leading cause of cancer deaths. Chemoresistance, particularly against platinum compounds, contributes to a poor prognosis. Histone deacetylase inhibitors (HDACi) and heat shock protein 90 inhibitors (HSP90i) are known to modulate pathways involved in chemoresistance. This study investigated the effects of HDACi (panobinostat, LMK235) and HSP90i (luminespib, HSP990) on the potency of cisplatin in ovarian cancer cell lines (A2780, CaOV3, OVCAR3 and cisplatin-resistant sub-clones). Preincubation with HDACi increased the cytotoxic potency of HSP90i, whereas preincubation with HSP90i had no effect. Preincubation with HSP90i or HDACi 48h prior to cisplatin enhanced the cisplatin potency significantly in all cell lines via apoptosis induction and affected the expression of apoptosis-relevant genes and proteins. For CaOV3CisR and A2780CisR, a preincubation with HDACi for 48–72 h led to complete reversal of cisplatin resistance. Furthermore, permanent presence of HDACi in sub-cytotoxic concentrations prevented the development of cisplatin resistance in A2780. However, triple combinations of HDACi, HSP90i and cisplatin were not superior to dual combinations. Overall, priming with HDACi sensitizes ovarian cancer cells to treatment with HSP90i or cisplatin and has an influence on the development of cisplatin resistance, both of which may contribute to an improved ovarian cancer treatment.